Adapted Nested Force-Gradient Integrators: The Schwinger Model Case. (8th March 2017) - Shcherbakov, Dmitry; Ehrhardt, Matthias; Finkenrath, Jacob; Günther, Michael; Knechtli, Francesco; Peardon, Michael
Abstract: We study a novel class of numerical integrators, the adapted nested force-gradient schemes, used within the molecular dynamics step of the Hybrid Monte Carlo (HMC) algorithm. We test these methods in the Schwinger model on the lattice, a well known benchmark problem. We derive the analytical basis of nested force-gradient type methods and demonstrate the advantage of the proposed approach, namely reduced computational costs compared with other numerical integration schemes in HMC.